TREATING DEPRESSION WITH COGNITIVE BEHAVIOR THERAPY - Tripathi, Jyoti Luxmi; Singh, Seema (International Journal of Psychosocial Rehabilitation, 2020)
Depression is a critical issue influencing around 121million individuals around the world. Depression is anticipated as the main source of disability and the second driving giver to the worldwide weight of sickness by the year 2020. It happens in people of all sexual orientations, ages, and foundations. A review by World Mental Health Survey Initiative has said that India has the most noteworthy significant prevalence rate of depression worldwide. Depression is an exceptionally basic and incapacitating condition. More than one out of eight individuals will have an episode of depression in a lifetime and most of the patients who have an episode of depression wind up having no less than one more scene later in life. Depression includes losing inspiration and enthusiasm for things, a diminished capacity to appreciate life, and feeling pitiful or down. Individuals experiencing depression may likewise have low vitality, an excessive amount of or too little craving for food, sentiments of blame and thoughts about death or even suicide. Depression can radically influence some individual’s capacity to work interpersonally, socially, and at work. It influences the lives of the sufferers, their families and guardians, and their managers and collaborators. From a more extensive view, it negatively affects the working of society at large. Depressions can happen at any age however ordinarily it starts from the mid adolescents, 20s, or 30s. In essential care settings, approximately 30% of patients report depressive manifestations. Cognitive Behavior therapy (CBT) was produced in the sixties as another treatment approach for depression. It is a sort of psychotherapy. This type of treatment alters thought designs with a specific end goal to change states of mind and practices. It depends on the possibility that negative activities or sentiments are the after effect of current twisted convictions or contemplations, not oblivious strengths from the past. CBT is a more fleeting methodology than psychoanalysis and psychodynamic therapies. Other therapies may require quite a while for revelation and treatment. CBT often requires just 10 to 20 sessions. The present paper is an endeavor to talk about the adequacy of CBT in the treatment of depression.